Application of Hot Fit Model to Analyze Information Technology Ams (Academic Management System) - Elmayati, Elmayati; Intan, Bunga; Nurdiansyah, Deni; Milenia, Aprilsa; Kelpin, Yogi (Politeknik Ganesha Medan, 2022)
Bina Insan University has applied a computer-based information system. This system is named AMS (Academic Management System). The application of AMS (Academic Management System) at this time is still experiencing various obstacles and obstacles at the level of user acceptance. This study aims to analyze the results of the evaluation of the success factors for implementing AMS (Academic Management System) using the Hot-Fit Model (Human Organization Technology – Net benefits). This model was chosen because this model can provide an explanation and provide an evaluation of the factors that influence the implementation of a system at the University of Bina Insan Lubuklinggau in terms of Human (Human), Organization (Organization), Technology (Technology), and Net benefits. In addition, the success of implementing AMS (Academic Management System) at the University of Bina Insan Lubklinggau, is also influenced by the support and encouragement from universities to AMS (Academic Management System) users, as well as the availability of adequate facilities within the Bina Insan Lubuklinggau University to use AMS (Academic Management Systems). From the analysis that has been carried out on 80 respondents who have filled out the research questionnaire, the results show that to test the validity of the variables (Human), Organization (Organization), Technology (Technology), and Net benefit, it shows that each question measured on all variables is valid, which indicated by Corrected Item – Total Correlation or (rcount) the entire score of Corrected Item – Total Correlation or (rcount) greater than rtable of 0.220, and for the F test results obtained a value of F = 13.334 with a significance of 0.000. meaning that the variables of human, organization and technology together have a significant effect on net-benefit (Y).